Advances on pathogenesis and prevention of enterotoxemia of alpacas - Rosadio A., Raúl (2012)
The results of our recent research work on enterotoxemia in Peruvian alpacas are presented. Microbiological and molecular analyses found that the majority of the isolates corresponded to Clostridium perfringens and contained the cpa coding gene for α toxin (A genotype) while 0.4% contained both the cpa and cpb genes of the α and β toxins (C genotype). A parallel study revealed that 8.5% of the genotype A isolates also had cpb2, but the cpe (enterotoxin) gene was absent in all cases. These results highly suggest that the exotoxins secreted by C. perfringens are the virulent factors in enterotoxemia, rather than the endogenous enterotoxin. Additionally, an histopathological study of intestinal samples from fatal cases showed that 30.6% had abundant immature structures of Eimeria macusaniensis affecting deep mucosa and cryptic gland epithelia, primarily in the jejune and ileum, suggesting that eimeriosis is likely a triggering or predisposing factor for the development of enterotoxemia. The microbiological studies allowed the design and progressive improvement of an inactivated enterotoxemia vaccine containing primarily the bacterial component plus exotoxins of types A, Aβ2 and C isolated from natural fatal cases of the disease. During six years of field tests in southern Peru, the vaccine has steadily reduced specific neonatal mortality rates due to enterotoxemia from 19.5% (2000, without vaccine) to less than 5% in 2006.